High-Mobility and High-Optical Quality Atomically Thin WS2. Issue 1 (December 2017) - Reale, Francesco; Palczynski, Pawel; Amit, Iddo; Jones, Gareth; Mehew, Jake; Bacon, Agnes; Ni, Na; Sherrell, Peter; Agnoli, Stefano; Craciun, Monica; Russo, Saverio; Mattevi, Cecilia
Abstract The rise of atomically thin materials has the potential to enable a paradigm shift in modern technologies by introducing multi-functional materials in the semiconductor industry. To date the growth of high quality atomically thin semiconductors (e.g. WS2 ) is one of the most pressing challenges to unleash the potential of these materials and the growth of mono- or bi-layers with high crystal quality is yet to see its full realization. Here, we show that the novel use of molecular precursors in the controlled synthesis of mono- and bi-layer WS2 leads to superior material quality compared to the widely used direct sulfidization of WO3 -based precursors. Record high room temperature charge carrier mobility up to 52 cm2 /Vs and ultra-sharp photoluminescence linewidth of just 36 meV over submillimeter areas demonstrate that the quality of this material supersedes also that of naturally occurring materials. By exploiting surface diffusion kinetics of W and S species adsorbed onto a substrate, a deterministic layer thickness control has also been achieved promoting the design of scalable synthesis routes.